2013
DOI: 10.1002/adfm.201203220
|View full text |Cite
|
Sign up to set email alerts
|

Bench‐Top Fabrication of Hierarchically Structured High‐Surface‐Area Electrodes

Abstract: Fabrication of hierarchical materials, with highly optimized features from the millimeter to the nanometer scale, is crucial for applications in diverse areas including biosensing, energy storage, photovoltaics, and tissue engineering. In the past, complex material architectures have been achieved using a combination of top‐down and bottom‐up fabrication approaches. A remaining challenge, however, is the rapid, inexpensive, and simple fabrication of such materials systems using bench‐top prototyping methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
144
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(157 citation statements)
references
References 41 publications
13
144
0
Order By: Relevance
“…While the sheet resistance demonstrated for the 25 nm gold thickness is still relatively high for some applications, other studies have shown that thicker wrinkled films (up to 200 nm) result in lower sheet resistances. 19 We have also shown that these wrinkled metallic structures provided a large amount of strain relief allowing otherwise brittle metallic films to stretch out to more than 200% with negligible changes in resistance of up to 100%. Even when compared to the more complex hybrid structures, 8 liquid metals, 10 and optimized geometries, 14 our simple wrinkled thin film wires are more robust to strain with significantly less change in resistance.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…While the sheet resistance demonstrated for the 25 nm gold thickness is still relatively high for some applications, other studies have shown that thicker wrinkled films (up to 200 nm) result in lower sheet resistances. 19 We have also shown that these wrinkled metallic structures provided a large amount of strain relief allowing otherwise brittle metallic films to stretch out to more than 200% with negligible changes in resistance of up to 100%. Even when compared to the more complex hybrid structures, 8 liquid metals, 10 and optimized geometries, 14 our simple wrinkled thin film wires are more robust to strain with significantly less change in resistance.…”
mentioning
confidence: 71%
“…The subsequent folds introduce a higher probability of contacting adjacent structures, thus resulting in lower sheet resistance. 16,19 Figure 2(d) shows the sheet resistance from unshrunken to transferred samples for our wrinkled thin film wires.…”
mentioning
confidence: 99%
“…4 These approaches include techniques such as razor-blade cutting (xurography), 6,7 adhesive film masking, 8 and structuring through shape-memory polymers (SMPs), 9,10 among many others. Using these techniques, it has been possible to prototype microfluidic channels, [11][12][13] pattern thin films and surfaces, 8,14 and produce micro and nanostructured metallic surfaces [15][16][17] that have been applied mostly to Surface Enhanced Raman Scattering (SERS) applications. [18][19][20] The simplicity and cost-effectiveness of bench-top fabrication methods make them ideal for prototyping, optimizing, and producing low-cost disposable LoC devices.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the uses for these materials include reducing the size of microfluidic channels and patterned surfaces, 21,22 and structuring thin films through compressive stress. 16,23,24 Our group 15,25 and others 20,26,27 have used the latter approach to structure gold films with features that are tuneable in the micro-to nanoscale. The structured gold films, when used as SERS substrates 20 or as working electrodes in an electrochemical setup, 15 present enhanced surface area that can significantly improve sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation